Crosstalk Between mRNA 3'-End Processing and Epigenetics - Soles, Lindsey V.; Shi, Yongsheng (Frontiers in Genetics, 2021)
The majority of eukaryotic genes produce multiple mRNA isoforms by using alternative poly(A) sites in a process called alternative polyadenylation (APA). APA is a dynamic process that is highly regulated in development and in response to extrinsic or intrinsic stimuli. Mis-regulation of APA has been linked to a wide variety of diseases, including cancer, neurological and immunological disorders. Since the first example of APA was described 40 years ago, the regulatory mechanisms of APA have been actively investigated. Conventionally, research in this area has focused primarily on the roles of regulatory cis-elements and trans-acting RNA-binding proteins. Recent studies, however, have revealed important functions for epigenetic mechanisms, including DNA and histone modifications and higher-order chromatin structures, in APA regulation. Here we will discuss these recent findings and their implications for our understanding of the crosstalk between epigenetics and mRNA 3’-end processing.